Twelve Tips to Mastering the Effective Elements of Peer Group Supervision: Practical Guidance from a Narrative Review and Expert Perspectives - Howarth, Stephanie; Ducat, Wendy; Neary, Alexandra (The Journal of Practice Teaching and Learning, 2025)
Abstract: Peer Group Supervision (PGS) is recognised as a valuable approach for supporting professional development, reflective practice, and workforce sustainability across diverse settings. Despite its increasing uptake, challenges remain in ensuring consistent, effective implementation. This paper presents twelve practical, evidence-informed tips to guide the effective implementation of PGS. Organised into foundational, supportive, and enhancing elements, the tips draw on literature and expert perspectives from health and community services. Key enablers such as, structure, trust, reflective practice, feedback, organisational support, and access to training, are addressed alongside common challenges including unclear purpose, group dynamics, and inconsistent attendance. These tips are intended to strengthen the quality and impact of PGS as a collaborative, scalable, and cost-effective supervision model.